An improved GRMOD heuristic for container loading problem - Ho, Ziao Fung; Lee, Lai Soon; Abdul Majid, Zanariah; Seow, Hsin Vonn (AIP Publishing LLC, 2013)
The Container Loading Problem (CLP) is a study of loading a subset of goods or parcels of different sizes into a three-dimensional rectangular container of fixed dimensions such that the volume of packed boxes is maximized. In this paper, an improved version of the modified George and Robinson heuristic (iGRMOD) is developed to solve the CLP. Comparison computational results on benchmark data set from the literature will be presented. The performances of the iGRMOD are superior than the GRMOD and other heuristics reported in the literature.